THE IMPACT OF MARKET REVITALIZATION ON THE SOCIO-ECONOMIC STATUS OF TRADERS IN NEW TURI MARKET - Heru Irianto; Tri Prasetijowati; Bagus Ananda Kurniawan; Lusiani Putri Anggraini (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2024)
The revitalization of Pasar Turi Baru in Surabaya City is a response to the unfit condition of the market due to fire in 2007. The purpose of this research is to analyze the implementation of market revitalization, its impact on the socio-economy of traders, and the optimization of government policies in the revitalization program of Pasar Turi Baru in Surabaya City. This research method uses a qualitative method with a descriptive approach, using purposive sampling to select informants. The data were collected through interviews and documentation, and the analysis included data reduction, data presentation, and conclusion drawing. The results showed that the revitalization of Pasar Turi Baru was carried out through several stages, including planning to the opening of the market. This revitalization involves changes such as buildings, facilities, and market amenities. In addition, there are non-physical changes, such as the rights and obligations of traders, placement procedures, trader financing, market management services, social interactions, and trader income. However, there are still some obstacles after revitalization, such as land utilization that has not been maximized, facilities that are less than optimal, toilet cleanliness that is not maintained, difficulties for traders to get capital loans, and the influence of events and promotions. The revitalization of Pasar Turi Baru has had a positive socio-economic impact on the traders, such as increasing the feasibility and comfort of their business, opening up jobs, and changing their status to legal traders. However, there are also negative impacts, namely a decrease in income and an increase in operational costs. To maximize the results of revitalization, Pasar Turi Baru made several efforts, such as the selection of an experienced workforce, the use of a good financial program, the application of professional SOPs, training for market management employees and traders, and regular maintenance of market facilities.